Characterizing the Association Between Alcohol and HIV Virologic Failure in a Military Cohort on Antiretroviral Therapy. (25th February 2016) - Deiss, Robert G.; Mesner, Octavio; Agan, Brian K.; Ganesan, Anuradha; Okulicz, Jason F.; Bavaro, Mary; Lalani, Tahaniyat; O'Bryan, Thomas A.; Bebu, Ionut; Macalino, Grace E.
Abstract : Background: The effects of at‐risk drinking on HIV infection remain controversial. We investigated the impact of self‐reported alcohol consumption on surrogate markers of HIV progression among individuals initiated on highly active antiretroviral therapy (HAART). Methods: We analyzed individuals who were surveyed on alcohol use within a year of HAART initiation between 2006 and 2014. At‐risk drinking was defined as consumption of at least 3 or 4 drinks/d, or 7 and 14 drinks/wk among women and men, respectively. We performed time‐updated generalized estimating equation logistic regression to determine the effect of at‐risk drinking on virologic failure (VF) and mixed‐effects linear regression on CD4 count reconstitution, controlling for potential confounders. Results: Of 801 individuals initiated on HAART, 752 individuals with alcohol survey data were included in the analysis. Of these, 45% ( n = 336) met criteria for at‐risk drinking at HAART initiation on at least 1 survey. The rates of VF were 4.30 per 100 person‐years (95% CI [2.86, 6.21]) for at‐risk drinkers and 2.45 per 100 person‐years (95% CI [1.57, 3.65]) for individuals without at‐risk drinking. At‐risk drinking was not significantly associated with VF (OR 1.73, 95% CI [0.92, 3.25]) ( p = 0.087) or CD4 reconstitution (CD4 increase 11.4; 95% CI [−19.8, 42.7]) in univariate analyses; however, in our multivariate model, a statistically significant relationship between VF and at‐risk drinking was observed (OR 2.28, 95% CI [ 1.01, 5.15]). Conclusions: We found a high proportion of at‐risk drinking in our military cohort, which was predictive of VF in multivariate analysis. Given alcohol's effect on myriad HIV and non‐HIV outcomes, interventions to decrease the prevalence of at‐risk drinking among HIV‐infected individuals are warranted. Abstract : We investigated the impact of self‐reported alcohol consumption on surrogate markers of HIV progression among individuals initiated on highly active antiretroviral therapy (HAART). As noted in this figure, at‐risk drinking was associated with virologic failure in multivariate, though not univariate, analyses. Together, our data demonstrate a moderate association between at‐risk drinking and virologic failure, likely mediated by factors including severity of drinking.